Possible impacts of anthropogenic climate change to the upwelling in the South Brazil Bight - Mihael Machado de Souza; Moritz Mathis; Bernhard Mayer; Maurício Almeida Noernberg; Thomas Pohlmann (Climate Dynamics, 2020)
Anthropogenic climate change is expected to strengthen upwelling events worldwide, driven by an increase of upwelling-favorable winds. However, Earth System Models (ESM) tend to underestimate regional processes due to their coarse grid resolution, which can lead to local biases. We use a high-resolution ocean model ( $${1/12}^{° }$$ 1 / 12 ∘ ) forced by results from the Max-Planck-Institute-ESM to analyze the impact of the RCP8.5 emission scenario on the upwelling of South Atlantic Central Water (SACW) in the South Brazil Bight (SBB). We find a stronger Ekman forcing and a higher spread of SACW over the shelf, but this does not translate into higher vertical velocities at the bottom of the mixed-layer in the end of the century. The increased winds’ effect is essentially balanced by an increase in water column stability due to the surface warming. This is particularly important during austral summer, when this process tends to weaken the upwelling. Vertical velocities decrease significantly along the shelf break. Here, the upwelling regime is governed by the Brazil Current (BC) and slight changes in transport induce large responses in upwelling strength. The consequences are increased sea surface temperatures over most of the shelf, although mitigated by the SACW upwelling and kept below global projections. However, temperatures decrease along Cabo Frio. In this region, shelf break upwelling dominates and is enhanced by a local increase in the BC transport. This highlights the importance of regional processes and, more specifically, of changes in the BC transport for the upwelling in the SBB.

Driving mechanisms of the variability and long-term trend of the Brazil–Malvinas confluence during the 21st century - Mihael M. de Souza; Moritz Mathis; Thomas Pohlmann (Climate Dynamics, 2019)

Which complexity of regional climate system models is essential for downscaling anthropogenic climate change in the Northwest European Shelf? - Moritz Mathis; Alberto Elizalde; Uwe Mikolajewicz (Climate Dynamics, 2018)